(untitled) (Semiárida, 2020)
The garlic (Alium sativum L.), it is a species belonging to the family of the Allied. Argentina is one of the principal producing countries and the second world exporter of garlic, after China, the major quantity is exported from January to June, To evaluate the culture, in not traditional zones as La Pampa, it is a valuable contribution, where environmental factors conjugate not alone but also characteristics of soil, quality of water, managing of culture, workforce, and response to fertilization, plagues, diseases, crop, yields and marketing. The aim of the work was to evaluate the productive behavior of two clowns of garlic, "Chinese" and "Colorado" and his response to the fertilization with sulphate of ammonium in one and two applications. The plantation was realized in the garden of the Facultad de Agronomía, UNLPam, April 15, 2005, in a design of complete blocks at random by 4 repetitions, the experimental unit consisted of a plot of two lines of 5 m. Of length, to 0.60 m between lines, with two lines of bordure. There were fertilized by sulphate of ammonium 30/7 in the treatments 1 (the only application) and 2, and 30/9 in the treatment 2 (double application) because of 50 kg.ha-1 every time. The values were compared by means of ANOVA, and Tukey’s test with a = 0,05. Bearing in mind the weight of dry clean garlic, the results indicate that both clowns answered favorably to the double fertilization, obtaining significant differences between treatments, obtaining major production with double fertilization, with regard to the unique fertilization, and in turn the plots with an alone fertilization produced more in weight that the plots witness without fertilizing. Also significant differences between clowns were obtained. The results reveal the major yield of the "Chinese" clown in the different treatments respect of the clown "Colorado".